2012
DOI: 10.1021/ac3014077
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Temperature-Selected Mass Spectra in Matrix-Assisted Laser Desorption Ionization of Peptides

Abstract: Matrix-assisted laser desorption ionization of peptides was investigated using α-cyano-4-hydroxycinnamic acid as the matrix. In each experiment, a set of mass spectra was collected by repetitive irradiation of a spot on a sample. Even though shot-to-shot variation in spectral pattern was significant, it was reproducible for different spots and samples. Each spectrum was tagged with the temperature in the early plume (T(early)) estimated through kinetic analysis of the peptide ion survival probability. T(early)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 34 publications
2
73
0
Order By: Relevance
“…We took the temperature in the early plume (T early ) [12] where in-source decay [13] occurred as the representative temperature of each MALDI event. We then found that the observed spectral changes were correlated with the lowering of T early as the sample became thinner upon repetitive irradiation [10]. 2.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…We took the temperature in the early plume (T early ) [12] where in-source decay [13] occurred as the representative temperature of each MALDI event. We then found that the observed spectral changes were correlated with the lowering of T early as the sample became thinner upon repetitive irradiation [10]. 2.…”
Section: Introductionmentioning
confidence: 82%
“…The vacuum-drying of such a solution is known to produce a rather homogeneous solid sample [10,11]. When we repetitively irradiated a spot on such a sample with laser pulses, we observed that the abundance of each ion appearing in the mass spectrum, both analyteand matrix-derived, changed systematically.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…4,5 In contrast, in the second group, photo-excitation is simply an instantaneous way of supplying thermal energy to the sample and hence inducing its ablation. [6][7][8][9] The thermal energy needed for ablation is supplied by photo-excitation in the first group of hypotheses also. Ionization of matrix molecules via pooling of excitons is the leading hypothesis belonging to the first group, while thermal processes such as the pre-formed ion emission have been proposed for the second group.…”
Section: Matrix-assisted Laser Desorption Ionization (Maldi)mentioning
confidence: 99%